1998
DOI: 10.1152/ajpheart.1998.275.4.h1351
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular acidosis differentially regulates KV channels in coronary and pulmonary vascular muscle

Abstract: Decreases in intracellular pH (pHi) potently dilate coronary resistance arteries but constrict small pulmonary arteries. To define the ionic mechanisms of these responses, this study investigated whether acute decreases in pHi differentially regulate K+ currents in single vascular smooth muscle (VSM) cells isolated from rat coronary and pulmonary resistance arteries. In patch-clamp studies, whole cell K+ currents were elicited by 10-mV depolarizing steps between −60 and 0 mV in VSM cells obtained from 50- to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
(66 reference statements)
1
43
1
1
Order By: Relevance
“…Changing the pH of the perfusate from 7.4 to alkaline pH resulted in an increase of coronary perfusion pressure in both WKY and SHR, confirming previous reports (5,19). However, effects of acidic pH on coronary arteries in normotensive rats have been controversial (8,18). Moreover, previous reports paid no attention to the blood pressure in rats.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Changing the pH of the perfusate from 7.4 to alkaline pH resulted in an increase of coronary perfusion pressure in both WKY and SHR, confirming previous reports (5,19). However, effects of acidic pH on coronary arteries in normotensive rats have been controversial (8,18). Moreover, previous reports paid no attention to the blood pressure in rats.…”
Section: Discussionsupporting
confidence: 76%
“…Vasoactive responses to acidification in vascular smooth muscles are often opposite, i.e., relaxation and contraction. Opposite responses are likely to be due to differences in vascular bed and species (3,7,8). However, effects of pH i on vascular smooth muscles have been unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current-density data and the voltage dependence of the I K in PASMCs in this report are within the range published in the literature. [25][26][27][28] Variability in these values can be explained in part by differences in the enzymatic dispersion techniques and the specific vascular sections used, because there is regional diversity in the expression of K ϩ channels within the pulmonary circulation. 28 In addition to the long-term effects of DCA, we show that this drug can increase I K in the short term much more rapidly and at much lower doses than previously described (mol/L versus mmol/L), indicating novel and previously unrecognized properties of DCA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the intracellular free H + could vary in response to different stimuli. Evidences indicated that intracellular protons could serve as a second messenger in regulating multiple cellular functions [22,23] .…”
Section: Discussionmentioning
confidence: 99%